Labor and the growth crisis in Sub-Saharan Africa - Lindauer, David L., 1952- 1952- (The World Bank, 1995)
The report "World Development Report 1995: workers in an integrating world" looks at what is required to improve labor outcomes in low- and middle-income economies. It identifies four areas in need of policy reform: 1) development strategy; 2) international integration; 3) labor market interventions; and 4) transformation to greater market orientation. This report considers the relevance of these policy areas to sub-Saharan African circumstances. Three key messages emerge: 1) a market-based approach to development, by expanding markets and encouraging more productive investments, will be a labor-demanding strategy in Africa as it has been elsewhere and is key to improving labor outcomes; 2) sub-Saharan Africa has become increasingly marginalized in the world economy. It is in the interest of Africa's labor force that this trend be reversed and that the region increase its integration with and participation in global markets; 3) Domestic labor market policies, especially those governing workers in the public sector, need to be redesigned to encourage more efficient use of labor and nonlabor resources. Required are policies that better reflect the labor market conditions in individual economies. This report begins with a review of labor market outcomes in sub-Saharan Africa. It then analyzes what is required to realize more rapid economic growth through the increased accumulation and productivity of physical and human capital. It examines Africa's role in the world economy and why greater integration is essential to the region. It discusses the role of labor policies directed at both private and public employers and considers how sub-Saharan African workers are affected by the transition from closed to more open development strategies. It concludes with a brief review of the prospects for Africa's growing labor force